Eksistensi Kesenian Kuda Lumping Grup Budi Lestari di Kelurahan Talang Betutu Kecamatan Sukarami Kota Palembang - Aisyah, Nyayu Sari; Kurniawan, Irfan; Siswanto, Silo (Indonesian Research Journal on Education, 2023)
This study aims to determine the existence of the Kuda Lumping Art of the Budi Lestari Group inTalang Betutu Village, Sukarami District, Palembang City. The method used in this research is descriptive qualitative with research objects or informants, namely studio owners, trainers, players and the community. Data collection techniques used in this study include observation,documentation and interviews. The results in this study are focused on the level of the Budi LestariGroup's Kuda Lumping Art among the community, especially the Talang Betutu community. From the results of the study it can be concluded that the Budi Lestari Group's Kuda Lumping is a Kuda Lumping Art Show that has been passed down from generation to generation and can be categorized as The existence of some of the Transmigration communities in Talang Betutu is proven that the Kuda Lumping Budi Lestari Group has been around for a long time, namely in 1977 and some people already know about it.